EFEKTIFITAS PEMBERIAN MINUMAN SEHAT MADU SOYA BEAN TERHADAP PERUBAHAN HB PADA IBU HAMIL TRIMESTER Ill UNTUK MENCEGAH KELAHIRAN BAYI STUNTING - yuniza yuniza (IKesT Muhammadiyah Palembang, 2023)
ABSTRACT Introduction: Pregnant women experience physical and psychological changes that can cause discomfort, especially in the second and third trimesters. In the third trimester, pregnant women need more nutrition to increase fetal weight development. Pregnant women have higher nutritional needs than non-pregnant women. The nutritional adequacy of pregnant women and the growth of their womb can be measured based on their weight gain. To meet nutritional needs, mothers must consume appropriate foods that contain lots of nutrients, because these foods are needed for fetal growth, placenta and metabolic growth. Poor nutrition during pregnancy can put pregnant women at risk of various complications, such as anemia, bleeding, the mother not gaining normal weight, and also the risk of giving birth to a child who suffers from nutritional problems, which is a risk factor for stunting. To increase energy, pregnant women can consume honey because honey contains sufficient calories and can increase the body's metabolism. The combination of honey and soybeans can be an alternative in increasing the weight of pregnant women. Objective: to determine the effectiveness of giving MaSoy on changes in HB as a prevention of the birth of stunted babies. The output of this research is a MaSoy product that can be marketed to prevent pregnancy anemia which interferes with weight gain in pregnant women and risks the birth of stunted babies. Method: This research is quantitative research with a quasi-experiment design with a one group pre and post test design approach. The population in this study was pregnant women in the third trimester. The sample in this study used a purposive sampling technique with a total of 41 respondents. Result: value .0047, which means that the value is <0.05 and this proves that there is an influence of soya honey drinks on HB levels in third trimester pregnant women. In this case it states that Ha is accepted and Ho is rejected. Conclusion: There is an effect of healthy soya bean honey drinks on Hb levels in third trimester pregnant women to prevent the birth of stunted babies. Keywords: Pregnant women; HB; Honey and Soya Bean; Stunting.